2018
DOI: 10.1016/j.ynstr.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute stress on the calibration of persistence

Abstract: People frequently fail to wait for delayed rewards after choosing them. These preference reversals are sometimes thought to reflect self-control failure. Other times, however, continuing to wait for a delayed reward may be counterproductive (e.g., when reward timing uncertainty is high). Research has demonstrated that people can calibrate how long to wait for rewards in a given environment. Thus, the role of self-control might be to integrate information about the environment to flexibly adapt behavior, not me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 64 publications
1
15
1
3
Order By: Relevance
“…We observed that the smaller were changes in hair cortisol level between the months of the study and higher were the life change units (from the questionnaire) the less subjects were choosing the later option. Among curvilinear relationships we did not confirm previous results about subjects’ earnings (Lempert et al, 2018a), but found some evidence for the reaction times: when chronic stress level increased slightly, it took longer for participants to decide in the short delay task, but when the cortisol measure from hair samples increased to higher levels, they decided quicker whether to pick a sooner or later option. Nevertheless, tests for curvilinear relationships included only a small portion of participants, those for whom there was an increase in biological stress level compared to the baseline.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We observed that the smaller were changes in hair cortisol level between the months of the study and higher were the life change units (from the questionnaire) the less subjects were choosing the later option. Among curvilinear relationships we did not confirm previous results about subjects’ earnings (Lempert et al, 2018a), but found some evidence for the reaction times: when chronic stress level increased slightly, it took longer for participants to decide in the short delay task, but when the cortisol measure from hair samples increased to higher levels, they decided quicker whether to pick a sooner or later option. Nevertheless, tests for curvilinear relationships included only a small portion of participants, those for whom there was an increase in biological stress level compared to the baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the literature, we expected significant medium level correlation between hair and saliva measures around r = 0.4 (Vanaelst et al, 2012; van Holland et al, 2012; Zhang et al, 2018; Weckesser et al, 2019) and low level to no correlation between biological measures and questionnaires (Vanaelst et al, 2012; Stalder et al, 2017; Prado-Gascó et al, 2019). Some scholars suggest log-transformation of cortisol values to better approximate a Gaussian distribution of cortisol values across subjects (Lenow et al, 2017; Lempert et al, 2018a). Indeed, we decided it is reasonable to modify all of our cortisol values based on the distributions before and after log-transformation (SI, Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations